MEDIA SOSIAL SUKSESKAN PROMOSI - Wahjoe Mawardiningsih (Universitas Sahid Surakarta, 2019)
Entrepreneurs need to actively follow market trends and look for opportunities to continue to thrive. Promotion must be in accordance with the conditions of the times. The virtual world in the form of social media needs to be empowered optimally for promotional media, in the form of media outlets: Facebook, Twitter, YouTube, corporate blog, Whatsapp, Line, Instagram. The use of social media for media promotion, can be combined using, not just one type. This will have a very positive impact